Parashuram Temple - Ghosh, Ayan (2023)
The site of Parashuram Temple was once a garden owned by a lady, Hariganga Ranchhoddas Bhansali. She donated the land in February 1965 and the Parashuram Temple was built in that space overlooking the western steps of Banganga Tank. Parashuram is an avatar of Lord Vishnu. The Skanda Purana mentions how Parashuram threw his parashu (battle axe) into the sea to reclaim the narrow strip of land along the Konkan coast, starting from Maharashtra all the way to Kerala, which is also known as Parashuram-kshetra.